Allocation of legal reserves of the paper and pulp company Suzano S.A. based on territorial planning in São Paulo state, Brazil - Rodrigues, Nathalia Maria Lins [UNESP] (2022)
Legal Reserves (RL) determine a percentage of native vegetation that needs to be maintained in rural properties in Brazil. It can be compensated or allocated by restoring the vegetation on the property itself or in another one. The large-scale restorations projects have a high cost, so it is important to develop forest restoration methodologies that assist in decision making, to identify factors and to map possibilities of allocation of RL. Thus, we aimed to map priority areas for allocating legal reserves and for restoration, a problem of land planning in a general position, applying it to an specific example of the company Suzano S.A. as a case study, the largest pulp and paper company in Latin America, and to discuss the applicability of used criteria. We expect that this methodology would show how much priority and where legal reserves should be allocated, in order to comply with Brazilian legislation. For that, we used Geographic Information System (GIS) and Multiple-Criteria Decision Analysis (MCDA). Selection of criteria was based on territorial planning that assist in forest restoration and of importance to Suzano and they were analyzed by a Hierarchical Analytical Process (AHP) to differentiate the importance of each criterion. According to the Brazil forest code, priority areas for RL allocation should consider river basin plans, Ecological-Economic Zoning, ecological corridors connection with protected areas, sites with greatest importance for the conservation of biodiversity and areas of environmental fragility. We found that most part of the state was classified as lower importance priority areas. Instead, current location of Suzano Legal Reserves is mostly in areas that have higher priorities for RL allocation. Thus, allocation or compensation of environmental debts in other basins, as the New Forest Code allows, should be taken with care, as legal reserves might be placed in low priority areas. Critic watersheds criteria determined the outcomes, but also the priority areas defined by São Paulo state. In the beginning of the UN Decade on Restoration, this study provides inputs to regularize rural properties and for increasing native vegetation cover.